2012
DOI: 10.1099/vir.0.040824-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro studies on the antiviral activities of viperin against influenza H1N1 virus infection

Abstract: Influenza A virus has caused a number of pandemics in past decades, including the recent H1N1-2009 pandemic. Viperin is an interferon (IFN)-inducible protein of innate immunity, and acts as a broad-spectrum antiviral protein. We explored the antiviral activities and mechanisms of viperin during influenza virus (IFV) infection in vitro and in vivo. Wild-type (WT) HeLa and viperinexpressing HeLa cells were infected with influenza A/WSN/33/H1N1 (WSN33) virus, and subjected to virological, light and electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 39 publications
(59 reference statements)
3
53
0
Order By: Relevance
“…We and others have demonstrated that viperin is induced by infection with a number of diverse viruses as well as able to limit viral infection in most instances, including the first reported up-regulation of viperin in human cytomegalovirus (HCMV) infected cells [8], [9], [10]. Subsequently, viperin has been shown to have anti-viral actions in other viral infections such as hepatitis C virus (HCV), influenza virus, human immunodeficiency virus (HIV), sindbis virus (SINV), the flaviviruses Japanese encephalitis virus (JEV) and West Nile virus (WNV) [9], [10], [11], [12], [13], [14], [15] and more recently, Bunyamwera virus [16] and Chikungunya virus [17]. The roles and actions of viperin in these different viral infections appear diverse and multifaceted with anti-viral activity in some cases dependent on alterations to lipid rafts (influenza, [14]), membrane localisation (HCV, [9]), the radical S -adenosylmethionine (SAM) enzymatic activity of viperin (HIV, [10]), negated by viral proteins (JEV, [11]) and even an enhancing role under some conditions for HCMV [18].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have demonstrated that viperin is induced by infection with a number of diverse viruses as well as able to limit viral infection in most instances, including the first reported up-regulation of viperin in human cytomegalovirus (HCMV) infected cells [8], [9], [10]. Subsequently, viperin has been shown to have anti-viral actions in other viral infections such as hepatitis C virus (HCV), influenza virus, human immunodeficiency virus (HIV), sindbis virus (SINV), the flaviviruses Japanese encephalitis virus (JEV) and West Nile virus (WNV) [9], [10], [11], [12], [13], [14], [15] and more recently, Bunyamwera virus [16] and Chikungunya virus [17]. The roles and actions of viperin in these different viral infections appear diverse and multifaceted with anti-viral activity in some cases dependent on alterations to lipid rafts (influenza, [14]), membrane localisation (HCV, [9]), the radical S -adenosylmethionine (SAM) enzymatic activity of viperin (HIV, [10]), negated by viral proteins (JEV, [11]) and even an enhancing role under some conditions for HCMV [18].…”
Section: Introductionmentioning
confidence: 99%
“…It was first identified as a gamma interferon (IFN-␄)-inducible protein which is directly induced by human cytomegalovirus (HCMV), and its constitutive expression is low (1). The viperin gene (also known as cig5 or RASD2) can also be categorized as an antiviral interferon-stimulated gene (ISG) which limits the replication of many DNA and RNA viruses (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, whether viperin plays a role during herpes simplex virus 1 (HSV-1) infection is unknown.…”
mentioning
confidence: 99%
“…Viperin restricts the replication of many RNA viruses, including HIV, hepatitis C virus (HCV), SeV, and influenza virus, and also DNA virus HCMV (1,2,9,11,14,15,37). Viperin effectively affects the replication of influenza virus by inhibiting its release from the plasma membrane of infected cells (10) and inhibits HCV replication by localizing and interacting with HCV nonstructural protein 5A at the lipid-droplet interface (6).…”
mentioning
confidence: 99%
“…Work characterizing the IFN-regulated gene Viperin (virus inhibitory protein, endoplasmic reticulum-associated, IFN-inducible, or RSAD2 ) has demonstrated that this protein can inhibit both RNA and DNA viruses (155–158). Viperin can decrease HCMV late gene expression, block the release of Influenza A and HIV-1 particles from the cell, and limit the replication of HCV, dengue virus, and WNV [reviewed in Ref.…”
Section: Viperinmentioning
confidence: 99%
“…Importantly, in vitro data show that Viperin inhibits Influenza A budding by disrupting cell membrane lipid raft integrity and increasing membrane fluidity. A key feature of this mechanism is the binding of Viperin to the sterol pathway enzyme farnesyl diphosphate synthase (FDPS)—an enzyme integral to sterol biosynthesis and the processes of farnesylation and geranylgeranylation (156, 158). Together, these observations suggest Viperin functions to inhibit Influenza A release via regulation of the sterol metabolic network; however, a precise mechanism has yet to be determined.…”
Section: Viperinmentioning
confidence: 99%